Benzylic deuteration of alkylnitroaromatics via amine‐base catalysed exchange with deuterium oxide. (16th December 2022) - Maddocks, Stephen; Samuri, Nurul F.; Ridge, Katerina; Cunningham, Ian D.; Lockley, William J. S.
Abstract : This paper describes the deuterium‐labelling of alkylnitroaromatics by base‐catalysed exchange with deuterium oxide. As the alkyl protons alpha to the aromatic ring are the most acidic sites in the molecule, regioselective hydrogen isotope exchange at this benzylic location leads to a regiospecifically deuterated product. The exchange labelling takes place in good yields and with high atom% abundance in the presence of an appropriate nitrogen base. Alkylated 2, 4‐dinitrobenzenes deuterate at room temperature under catalysis by triethylamine, whilst alkylated 2‐nitro‐ or 4‐nitrobenzenes and related mono‐nitroaromatics require higher temperatures and catalysis by 1, 5‐diazobicyclo[4.3.0]non‐5‐ene (DBN). The labelling reactions require an inert gas atmosphere, but otherwise are simple and high yielding with no obvious byproducts. Those compounds in which the benzylic protons are in an ortho ‐orientation with respect to the nitro group label somewhat more slowly than the analogues where there is a para relationship. In addition, higher alkyl homologues undergo benzylic deuteration at slower rates than methyl. Abstract : The alkyl groups of alkylnitroaromatics can be deuterated in the benzylic positions by isotopic exchange with deuterium oxide under catalysis by amine bases. Alkyldinitroaromatics label well at room temperature with triethylamine as catalyst, whereas mononitro sytems require a stronger base (DBN) and higher temperatures.